Eco-Efficiency: from vision to reality - Hershey, Clair H. (International Center for Tropical Agriculture, 2012)
The notion of eco-efficiency – first put forward by the private-sector at the time of the 1992 Earth Summit – has since been taken up by experts in agriculture as a guiding principle for research. Eco-efficient agriculture, according to a CIAT report, is competitive and profitable as well as sustainable and resilient, thus generating multiple benefits for the poor, especially when it offers new options for women. The concept seems especially relevant today, as leaders and organizations around the world – on the 20th anniversary of the Earth Summit – seek to renew global commitment to sustainable development against a troubling background of fragile food security and growing pressure on the environment. To foster debate and action, CIAT has prepared a major scientific publication titled Eco-Efficiency: From Vision to Reality, which is the inaugural volume in a new series called Issues in Tropical Agriculture. The publication documents recent advances in research on key production systems and crops, and it explores new avenues by which agricultural research can help achieve further gains in eco-efficiency.